ANALISIS PENGARUH VALUE CONSCIOUSNESS DAN PRICE QUALITY ASSOCIATION TERHADAP PRIVATE LABEL BRAND PURCHASE INTENTION DENGAN ATTITUDE SEBAGAI VARIABEL INTERVENING - Rahmanita Rahmanita; Jekky Gunawan (Journal of Accounting and Management Innovation, 2017)
The retail business has grown quite rapidly from year to year and encourages retailers launch private label products to strengthen its competitiveness. This study aimed to analyze the influence of value consciousness and price-quality association towards private label brand purchase intention with attitude as intervening. This study used a sample of 210 respondents who are shopping at shopping centers such as Giant, Hypermart, and Carrefour. The statistical methods used in analyzing the data is a multiple regression model. Sampling technique used was convenience sampling technique. The research data that has been collected tested using the program Statistical Package for Social Sciences (SPSS) v.21. The results of this research show a positive influence value consciousness and price quality association of the private label brand purchase intention either directly or indirectly through attitude as intervening.Keywords : private label brands, attitude, purchase intention, value consciousness, price-quality association.